Analisis Implementasi Sistem Informasi Akuntansi Penggajian Pegawai Pemerintah dengan Perjanjian Kerja pada Dinas Kesehatan Kota Bandung - Shafira Firdauza Queenta; Dwi Jayanti (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This study examines the implementation challenges of the payroll accounting information system at the Health Office of Bandung City, with a specific focus on salary disbursement and Additional Income Allowance (TPP) for Civil Servants with Work Agreements (P3K). The research addresses critical operational issues in public sector payroll management, including system efficiency, accuracy, and compliance with government regulations. The study identifies several key phenomena that occur both before and after disbursement periods, such as frequent employee inquiries about TPP payment schedules, questions regarding salary deduction details, and instances of payment discrepancies (both underpayment and overpayment). Using a qualitative descriptive methodology, the research employs multiple data collection techniques including in-depth interviews with key personnel, direct observations of payroll processes, and comprehensive document examination. The findings reveal that while the basic payroll procedure is operational, several areas require significant improvement. First, the documentation system needs enhancement to ensure better record-keeping and transparency. Second, internal control procedures require strengthening to prevent payment errors and improve accuracy. Third, staff training programs need development to enhance the technical competency of the payroll team.